Multivariate analysis of potential biomarkers of oxidative stress in Notopterus notopterus tissues from Mahanadi River as a function of concentration of heavy metals. (July 2016) - Mohanty, Deepali; Samanta, Luna
Abstract: In this study, investigation were done on the Mahanadi River water and health of dwelling Indian Knife fish Notopterus notopterus from three sites along the course of the river in an around Cuttack city (Odisha). Oxidative stress biomarker assays such as thiobarbituric acid reactive substances, protein carbonyls, protein and non-protein thionyls, reduced glutathione, metallothionein, superoxide dismutase, catalase, glutathione peroxidase/reductase couple, glutathione-S-transferase, and tissue metal (Fe, Cu, Ni, Cd, Pb and Zn) levels along with water quality assessments were assayed to measure the impacts on fish health. Results indicate that except Fe all other metals studied were within approved limits for fish liver and gill as approved by FAO/WHO. However, the muscle tissue do not have any metal beyond the permissible limit. A site and tissue specific response of the above mentioned oxidative biomarkers as well as metal accumulation in the fish tissues were noticed. Lipid peroxidation and protein carbonylation were increased gradually in the fish tissues collected from experimental sites along the course of the River in comparison to upstream reference site. Glutathione-S-transferase, glutathione peroxidase/reductase couple, reduced glutathione and non-protein thiol content were significantly decreased in fish tissues from experimental sites. An increase in metallothionein content was observed while superoxide dismutase and catalase showed tissue specific responses. Multivariate (Discriminant Function) analysis revealed that lipid peroxidation, protein carbonylation and superoxide dismutase have highest association as predictors of impact in the muscle and liver while that for gill is protein carbonylation, superoxide dismutase and glutathione reductase. Graphical abstract: Highlights: The concentrations of metal ions in the study sites are within permissible limit. Metal accumulation in the fish tissues is higher in the downstream sites. Higher oxidative stress observed in fish tissues collected from experimental sites. Protein carbonylation and superoxide dismutase may be used as biomarkers. In pollution monitoring programmes biomarker measurement should be included.